Метод расчета многоканальных лучевых переключателей с согласующим отрезком на входе - Oborzhytskyy, V. I. (PE "Politekhperiodika", Book and Journal Publishers, 2007)
A method is proposed for calculating the electrical parameters of elements of a multichannel beam-type switch, whose input matching is provided by a transforming section of the transmission line located at the input of the switch. Approaches are considered for accounting the influence of parameters of line segments that connect the branching outputs and the switching elements in each channel on the operating characteristics of the switch. The applicability of the proposed method is demonstrated through examples of calculation and simulation of two- and four-channel switches with different types of switching elements. multichannel switch, beam switch, switch matching, impedance transformation